Pengaruh Kepemimpinan Transformasional Terhadap Work Engagement Pada Organisasi Perusahaan - Andhika Banu Bismoko; James Christian Suwandi; Catharina Aprilia Hellyani (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
The current organization can not be separated from the role of members and leaders. In the running of an organization the role of the leader becomes the main factor needed in making the vision and mission of the organization, the organization's goals, and also regulates and directs its members to be able to work in accordance with the direction of the leader. However, nowadays leadership does not always go smoothly. There are several obstacles faced by a leader, especially after the Covid-19 pandemic era ended. The existence of these events makes the employees or members in the organization become unstructured. Therefore, transformational leadership is needed in organizations, especially those within the company so that the organization continues to run. The role of this transformational leadership can also increase the motivation and desire of members to keep working hard and develop more work engagement. This research was carried out using a literature study research methodology using 5 journals as data references and theory books. From the results of the analysis of the author's reference journals, it was found that the transformational leadership style applied by every organization in the company can affect employee performance or work engagement. Based on the literature study conducted, it can be interpreted that transformational leadership has a good influence on employee performance. Transformational leadership also provides space for employees to be able to create ideas that are creative, innovative, and more loyal to the company.